Restoring Theoretically Optimal Lumbar Lordosis Deduced from Pelvic Incidence and Thoracic Kyphosis has Advantages to Decrease the Risk of Postoperative Mechanical Complications in Adult Spinal Deformity - Wang, Jingyu; Zhang, Qianshi; Liu, Fubing; Yuan, Hui; Zhang, Yi; Wang, Xiaobin; Li, Jing (Frontiers in Surgery, 2022)
Objective: To establish a regression formula for LL based on individual PI and TK in asymptomatic population aged over 50 years and evaluate its predictive power for the occurrence of postoperative mechanical complications in patients with adult spinal deformity (ASD). Methods: A total of 178 asymptomatic adults were recruited for the study.The association between LL and PI, LL and TK, was investigated to establish a predictive formula for ideal LL based on PI and TK. Additionally,93 ASD patients undergoing posterior correction surgery were retrospectively analyzed.The absolute value of the gap between postoperative actual LL and theoretical LL was defined as ΔLL. Patients were classified into two groups depending on the presence or absence of mechanical complications.The demographic and radiological data of patients were compared between the two groups. Results:A significant association was found between LL and PI (r=0.599, P<0.001), LL and TK (r=0.523, P＜0.001). A novel formula was developed as follows: LL=0.7*PI+0.4*TK+1 (R2=0.524).In the validation cohort, 29 patients developed mechanical complications.Postoperative ΔLL (12.5±7.6°vs.7.0±5.4°,P=0.001) significantly increased the incidence of mechanical complications. The most appropriate threshold of ΔLL for predicting mechanical complications was 9.8°. For patients whose ΔLL were＜9.8° and ＞9.8°, the incidence of mechanical complications was 19.4% and 54.8%, respectively. Conclusion: Ideal lumbar lordosis should be matched for PI and TK. The developed prediction formula for LL based on PI and TK in asymptomatic adults may help surgeons to understand the mechanisms of lumbar alignment generation and predict occurrence of mechanical complications after ASD surgery.